Convergent crater circulations on Mars: Influence on the surface pressure cycle and the depth of the convective boundary layer. Issue 18 (30th September 2015) - Tyler, Daniel; Barnes, Jeffrey R.
Abstract Modeling of slope flow circulations in idealized axisymmetric craters is used to understand (1) the large surface pressure amplitude observed in Gale Crater by the Rover Environmental Monitoring Station and (2) the shallow convective boundary layer (CBL) suggested by Curiosity imagery. Air temperatures vary within craters with greater amplitudes than outside them, becoming warmer/colder during day/night. This crater circulation effect is most significant over the depth of the crater (key parameter). Within the idealized craters, a surface pressure cycle develops (in the real atmosphere it is enhanced). Partially caused by thermal expansion, a "surge" of mass away from the craters develops during daytime. Over crater floors, the CBL depth is inhibited by a capping inversion from the adiabatic warming of widespread daytime subsidence. For a variety of craters (radius, depth, and with or without a central mound), the results are very similar. In real‐atmosphere simulations over canyons or large basins, similar circulations are seen.